Effects of Self-efficacy, Health Perception, Social Support and Perceived Disability on Health Promoting Behavior of Nursing Students (Medico Legal Update, 2020)
Purpose: This study is a descriptive survey to investigate the relationship between health promotingbehaviors and self-efficacy, health perception, social support and perceived disability and to identify factorsaffecting health promoting behaviors among nursing students.Method: With the permission of the Education Committee of the Department of a University, 249 nursingcollege students explained the purpose and method of research and collected data with written consent. Thedata were analyzed by the t-test, ANOVA and Pearson’s correlation and Stepwise Multiple Regression usingthe SPSS 24.0 program.Results: The health promoting behaviors of the subjects were a positive correlation at the statically significantlevel at the self-efficacy (r=.73, p